New Insights into Gene Delivery to Human Neuronal Precursor NT2 Cells: A Comparative Study between Lipoplexes, Nioplexes, and Polyplexes - Agirre, Mireia; Ojeda, Edilberto; Zarate, Jon; Puras, Gustavo; Grijalvo, Santiago; Eritja, Ramón; García del Caño, Gontzal; Barrondo, Sergio; González-Burguera, Imanol; López de Jesús, Maider; Sallés, Joan; Pedraz, José Luis (Molecular pharmaceutics, 2015)
The transfection of human NTera2/D1 teratocarcinoma-derived cell line (or NT2 cells) represents a promising strategy for the delivery of exogenous proteins or biological agents into the central nervous system (CNS). The development of suitable nonviral vectors with high transfection efficiencies requires a profound knowledge of the whole transfection process. In this work, we elaborated and characterized in terms of size and zeta potential three different nonviral vectors: lipoplexes (144 nm; -29.13 mV), nioplexes (142.5 nm; +35.4 mV), and polyplexes (294.8 nm; +15.1 mV). We compared the transfection efficiency, cellular uptake, and intracellular trafficking of the three vectors in NT2 cell line. Lipoplexes exhibited the highest percentages of EGFP positive cells. The values obtained with polyplexes were lower compared to lipoplexes but higher than the percentages obtained with nioplexes. Cellular uptake results had a clear correlation with respect to the corresponding transfection efficiencies. Regarding the endocytosis mechanism, lipoplexes enter in the cell, mainly, via clathrin-mediated endocytosis (CME) while polyplexes via caveolae-mediated endocytosis (CvME). Nioplexes were discarded for this experiment due to their low cellular uptake. By simulating an artificial endosome, we demonstrated that the vectors were able to release the DNA cargo once inside the late endosome. The data collected from this assay showed that at 6 h the genetic material carried by polyplexes was still located in the late endosome, while DNA carried by lipoplexes was already in the nucleus. This result indicates a faster intracellular traffic of the lipid-based vectors. Overall, our work gives new insights into the transfection process of NT2 cells by different nonviral vectors as a first step in the development of ex vivo gene therapy platform.